BEHAVIOR OF SQUARE REINFORCED CONCRETE COLUMNS STRENGTHENED BY DIFFERENT LAYERS OF GLASS FRP SHEETS - KHDIR, MUHSIN KHALID; TAHA, BAHMAN OMAR; ABDULRAHMAN, AHMED REDHA (Journal of Duhok University, 2021)
The behavior of reinforced square concrete columns strengthened by specific layers of glass fiber reinforced polymer (FRP) sheets were investigated through an experiment by testing of thirteen variety of concrete columns that were axially loaded at their ends. The most variable thought of during this study were the quantity or number of layers of glass fiber reinforcement polymer sheets and also the effect of confinement techniques (fully wrapped, strip ties and spiral sheets). The test values were compared with the proposed equation of ACI 440.2R-02, for samples strengthened by one layer of GFRP sheet can upgrade the load carrying capacity of columns in numerous ways of strengthening (fully wrapped, strip ties and spirally) by 25.5%, 6.7% and 29.5% respectively compared to the control (unstrengthen) column. Be that as a result of it would, for columns strengthen by 2 layers of GFRP sheets (fully wrapped, strip ties and spirally) the load carrying capacity increases by 36.5%, 19.6% and 29.8% respectively. While, for 3 layers of strengthen sample the percent of enhancement in the load carrying capacity increases by 38.2%, 20.1% and 30.7% respectively. Finally, the load carrying capacity increases by 43.2%, 29.2% and 33.2% for different confinement techniques (fully wrapped, strip ties and spiral sheets) respectively if they are strengthened by 4 layers of GFRP sheets.